Praperlakuan secara Hidrotermal Limbah Lignoselulosa untuk Produksi Bioetanol Generasi Kedua (Pretreatment of Lignocellulose Wastes Using Hydrothermal Method for Producing Second Generation Bioethanol) - Al-Arofatus Naini; Nurwahdah Nurwahdah; Ratri Yuli Lestari; Sunardi Sunardi, Ph.D. (Jurnal Riset Industri Hasil Hutan, 2018)
The second generation of bioethanol derived from various cellulosic biomass materials is one of the latest renewable energy as the alternative of fossil fuel. The cellulosic waste based wood and non-wood materials are the most abundant natural resource on the earth, renewable, and inexpensive. Currently, second generation bioethanol development is still not optimally done due to various obstacles, especially the pretreatment process to eliminate lignin, influencing the conversion process of cellulose into reducing sugar. Hydrothermal method is one of lignocellulose pretreatments, which is widely developed because this method is relatively cheap and environmentally friendly with the utilization of water-based solvent. Hydrothermal methods performed at high temperature and pressure in a relatively short time are able to deconstruct the lignocellulose structure that enables cellulase enzymes to access cellulose for hydrolysis. This study discussed about the development of hydrothermal method for lignocellulose pretreatment process to increase production of second-generation bioethanol. Some aspects studied in this research were structural change, chemical composition, lignocellulosic crystallinity before and after hydrothermal processes, and hydrothermal effect on the production of reducing sugars. Hydrothermal method could be used and developed as an efficient and cheap method as the first treatment of lignocellulose waste in attempt to increase the production of bioethanol.